An overview on pollination of the Neotropical Poales - Marina Wolowski; Leandro Freitas (Rodriguésia)
Abstract Current phylogenetic hypotheses support that ancestral Poales were animal-pollinated and that subsequent shifts to wind pollination have occurred. Ten of the 16 Poales families are widely distributed in the Neotropics, however a comprehensive understanding of their pollination systems' diversity is still lacking. Here we surveyed studies on pollination biology of Neotropical species of Poales. Poaceae, Cyperaceae and Juncaceae are predominantly wind-pollinated but insect pollination also occurs. Thurniaceae and Thyphaceae fit on anemophily but empirical data are missing. Pollen flowers with poricidal anthers have evolved independently in Mayacaeae and Rapateaceae. Pollen- and nectar-flowers occur in Xyridaceae, which are mainly pollinated by bees. Eriocaulaceae flowers secrete minute quantity of nectar and are pollinated by "diverse small insects". Pollination of Bromeliaceae is carried out by a great variety of animal groups, mainly hummingbirds, and includes anemophily. The diversity in floral forms is very high within the order but more constant within the families. This trend indicates that many events of species diversification may have occurred without divergence in the pollination mode. Still, parallel shifts in pollination modes are found, including possible reversals to wind- or animal-pollination, changes in the type of pollinators (e.g. from hummingbirds to bee or bats) and the arising of ambophily.